Comparative Analysis of Digital Marketing and Conventional Marketing of NPK Blue Fertilizer Income in PT. XTY Company - Aditia Erick Cantona Simatupang; Reynaldi Adrian Ginting; Manaor Bismar Posman Nababan (Jurnal Ilmiah METHONOMI, 2026)
Market demand for fertilizers in the agricultural and plantation sectors continues to rise each year, prompting companies to seek efficient marketing methods to reach these markets. The marketing methods for Blue NPK fertilizer implemented by PT. XTY company are digital marketing and conventional marketing. This research focuses on analyzing business feasibility, income share, income comparative, and income comparisons from the marketing of Blue NPK fertilizer. The research was conducted at PT. XTY company in Medan using purposive sampling. The data collected were secondary data, specifically marketing data on Blue NPK fertilizer, obtained through documentation techniques. The study employed quantitative methods, including business feasibility analysis, income share analysis, income comparative, and income comparison analysis using a t-test with Stata 17 software. This research indicates that the business feasibility value of conventional marketing is higher than digital marketing, the percentage of income share for conventional marketing is higher than digital marketing, the percentage of income comparative for conventional marketing is higher than digital marketing, and there is a significant comparison in income between digital and conventional marketing. This research recommends that the company continue to optimize conventional marketing as it is more profitable for the business.